2021
DOI: 10.1186/s13039-020-00523-0
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Y as a marker for sex discrepancies in patients with organ transplants: a case report

Abstract: Background Organ transplantations cause discrepancy in results from cell-free DNA (cfDNA) testing, but scientific literature is scarce. Case A 33-year old gravida underwent cfDNA testing, which showed high levels of Y chromosome (ChrY) in the maternal bloodstream. The ChrY pattern was comparable to an adult male reference. As a result, cfDNA testing was only informative for autosomes. Routine 20-week ultrasound scan showed no structural alterations… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 16 publications
0
8
0
1
Order By: Relevance
“…Our literature search yielded eight articles published between January 1, 2008 and January 1, 2023 (Balaguer et al., 2021 ; Balslev‐Harder et al., 2017 ; Bianchi et al., 2015 ; Byers et al., 2019 ; Neofytou et al., 2018 ; Neufeld‐Kaiser et al., 2015 ; Wilkins‐Haug et al., 2018 ; Zhu et al., 2021 ) that included details of eight women who had received transplants from male donors prior to undergoing NIPS. These data are shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our literature search yielded eight articles published between January 1, 2008 and January 1, 2023 (Balaguer et al., 2021 ; Balslev‐Harder et al., 2017 ; Bianchi et al., 2015 ; Byers et al., 2019 ; Neofytou et al., 2018 ; Neufeld‐Kaiser et al., 2015 ; Wilkins‐Haug et al., 2018 ; Zhu et al., 2021 ) that included details of eight women who had received transplants from male donors prior to undergoing NIPS. These data are shown in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…For example, Balaguer et al. ( 2021 ) reported a pregnant woman who had received a bone marrow transplant in whom the fetal fraction based on the Y chromosome was 73.3%. They suggested that the Y chromosome can be used as a marker to account for sex discrepancies in pregnant women who have previously received organ transplants.…”
Section: Resultsmentioning
confidence: 99%
“…Du cfDNA pouvant être libéré par un organe greffé, les greffes d'organes représentent un risque de faux positif mais les f estimé es dans ce contexte sont souvent aberrantes au regard des valeurs attendues et permettent alors de de´ celer l'interférence [15].…”
Section: Une Analyse Applicable Dans De Nombreuses Circonstancesunclassified
“…Fetal sex discrepancy after NIPS compared with sonographic findings has been reported due to the contribution of donor solid organ and marrow transplant DNA. 29,30 More work is needed to characterize whether NIPS can be used reliably in the UTx population.…”
Section: Fetal Testingmentioning
confidence: 99%
“…It is possible that small fragment DNA originating from the transplanted organ and used to assay for common autosomal aneuploidy (trisomy 13, 18, or 21) and aneuploidy of sex chromosomes (eg, 45X, 47XXX) may contribute to abnormal results when none exists in the fetus. Fetal sex discrepancy after NIPS compared with sonographic findings has been reported due to the contribution of donor solid organ and marrow transplant DNA 29,30. More work is needed to characterize whether NIPS can be used reliably in the UTx population.…”
Section: Introductionmentioning
confidence: 99%